2017
DOI: 10.1098/rstb.2016.0062
|View full text |Cite
|
Sign up to set email alerts
|

Vision in dim light: highlights and challenges

Abstract: One contribution of 17 to a theme issue 'Vision in dim light'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…As an important determinant of fitness, animals evolved a wide range of visual adaptation to see in the dark (Nilsson, 2009;O'Carroll & Warrant, 2017;Thomas, Robison, & Johnsen, 2017;Warrant, 2017;Warrant & Nilsson, 2006). Nocturnal vision is known to rely on highly efficient light capture, both at the level of the lens and photoreceptor outer segments, and often 255 compromises spatio-temporal resolution by summation strategies of neuronal readout (Warrant, 1999;2017).…”
Section: Discussionmentioning
confidence: 99%
“…As an important determinant of fitness, animals evolved a wide range of visual adaptation to see in the dark (Nilsson, 2009;O'Carroll & Warrant, 2017;Thomas, Robison, & Johnsen, 2017;Warrant, 2017;Warrant & Nilsson, 2006). Nocturnal vision is known to rely on highly efficient light capture, both at the level of the lens and photoreceptor outer segments, and often 255 compromises spatio-temporal resolution by summation strategies of neuronal readout (Warrant, 1999;2017).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing canonical LMC responses and fly turning showed that pure contrast sensitivity underestimated behavioral responses to moving stimuli ( Figure 1C). Mechanisms such as spatial pooling or sensorimotor processing might account for this discrepancy [16,31,32]. Alternatively, the newly identified luminance information might provide a corrective signal to ensure contrast constancy.…”
Section: L3 Neurons Are Required For Motion Responses When Light Levementioning
confidence: 99%
“…Physiologically different LMC subtypes have been described in different species. For example, LMCs in bumblebees and butterflies exhibit sustained components [50,51], and motionsensitive neurons perform better than photoreceptor responses predict in the nocturnal hawkmoth [32,52]. Interestingly, presynaptic L2 and L3 calcium signals are highly reminiscent of sustained and transient calcium signals in bipolar cells of the vertebrate retina [53][54][55].…”
Section: A Role For Luminance In Image Processing Might Be a Common Fmentioning
confidence: 99%
“…In dim‐light conditions the visual signal‐to‐noise ratio is low, which dramatically affects the availability and the salience of visual cues (Narendra, Kamhi, & Ogawa, ; Warrant, ). Indeed, on moonless nights, light levels can decrease by up to 11 orders of magnitude compared to a cloudless day (O'Carroll & Warrant, ), making it a challenge to access reliable visual information. Nevertheless, animals active in low light environments use visual information for navigation (Narendra et al, ; Warrant & Dacke, ).…”
Section: Introductionmentioning
confidence: 99%